The Permanent-Income Hypothesis of the Demand for Money - Peterson, Richard E. (The Review of Economics and Statistics, 1972)
IN 1963 Nissan Liviatan tested the Permanent-Income Hypothesis (PIH) as an errors in variables model and used a combined crosssection time-series body of data consisting of the 1958-1959 Israel Reinterview Savings Survey. His findings were weakened (i) by the fact that a savings survey was used which meant that consumption was not independently estimated but rather was computed as a residual; hence, consumption and income had a common measurement error which thus violated a basic assumption of the model that the covariance between transitory income and transitory consumption is zero; and (ii) by the fact that, if the horizon is in fact three years, then income lagged one year cannot be used as an instrumental variable. Milton Friedman, in his rejoinder accompanying Liviatan's paper (1963), suggested that it would be most desirable that a Livia.tantype analysis be applied to data not marred by common errors of measurement and that such data span a three-year period so that income or consumption for one year could be used as an instrumental variable for a year at least two years later or earlier. In this paper both criteria will be met income and money demand are independently estimated and cross-section data covering a three-year period are used. In addition, this paper extends the PIH of aggregate consumption to individual consumer goods. The generalization results from relaxing Friedman's assumption of a linear homogeneous consumption function (unitary income elasticity). Since Friedman has elsewhere (1959) suggested that money can be looked on as a consumer durable, it will be money that this study uses as its consumer good. The methodology, however, is completely general and any other consumer good could have been chosen.